PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP HASIL BELAJAR MATA PELAJARAN IBADAH SISWA KELAS VII SMP MUHAMMADIYAH 2 SURAKARTA - Rosyid, Sahidna Ahmad; Hidayah, Nur (STKIP Pesisir Selatan, 2025)
This research aims to determine the effect of using audio visual learning media on student learning outcomes at SMP Muhammadiyah 2 Surakarta. the researcher used a type of quantitative research, with a correlation approach to determine the relationship between variable X and variable Y. Data collection technique used a questionnaire from 26 respondents. Sampling using saturated samples, Data analysis techniques using simple regression tests and determination coefficients. The hypothesis test uses the t-calculation formula. The results of the study showed that: (1) The used of audio visual learning media in class VII PK A SMP Muhammadiyah 2 Surakarta was included in the criteria with an average of 15. (2) The learning outcomes of the worship subject of class VII PK A SMP Muhammadiyah 2 Surakarta were included in the criteria with an average of 78; (3) Based on the results of the hypothesis test, the audio visual learning media showed a value of Sig. (0.054) > 0.05, then H0 was accepted and H1 was rejected, which means that the variable X (Audio Visual Learning Media) had no effect on the variable Y (Learning Outcomes of Grade VII PK A Junior High School Muhammadiyah 2 Surakarta).